Investigation on Sand and Cement Particles Reinforcement in Aluminium Matrix Composite (AMC) - Hamdan, Muhammad Aqil; Abdul Latif, Noradila (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The aerospace, automotive, nuclear, biotechnology, electrical, and sports goods sectors may all benefit from the usage of metal matrix composites (MMCs), a class of sophisticated materials. MMCs, which have advantages over base metal alloys in terms of characteristics, is composed of a non-metallic reinforcement integrated into a metallic matrix. These include enhanced heat conductivity, superior stiffness-to-weight and strength-to-weight ratios, abrasion resistance, creep resistance, dimensional stability, and resistance to creep. Additionally, they operate better in hot temperatures. To enhance the thermomechanical characteristics and performance of the lightweight but relatively soft host metal, hard and strong particles in the form of particulates or fibers are added. This study uses a mixed chip of AA7075 aluminum alloy with sand and AA7075 aluminum alloy with cement. In addition, cement and sand are used as mixing the material with AA7075 aluminum alloy with different percentages namely Chip AA7075 (97.5%) + (2.5%) cement or sand, Chip AA7075 (95%) + (5%) cement or sand , Chip AA7075 (92.5%) + (7.5%) cement or sand, Chip AA7075 (90.5%) + (10%) cement or sand, Chip AA7075 (87.5%) + (12.5%) cement or sand. Next, density, apparent porosity, water absorption, microhardness, compression, and microstructure analysis of aluminum matrix composites were identified in the current study. The results showed that the mixture of cement with aluminum alloy or the mixture of sand with aluminum alloy was very unsuitable because the results showed a decrease in microhardness during the experiment. This is evidenced when the micro-hardness of the mixture of aluminum alloy with cement decreased from 64.689 to 32.654 and the microhardness of the mixture of aluminum alloy with sand decreased from 55.540 to 34.452. Finally, the use of sand and cement is less suitable for mixing with aluminum alloys and can be replaced with other materials such as coconut fiber, rice husk, and so on.